2010
DOI: 10.1136/ard.2009.121426
|View full text |Cite
|
Sign up to set email alerts
|

Relation of synovitis to knee pain using contrast-enhanced MRIs

Abstract: Background It has been suggested that synovitis causes joint pain. On non-contrast-enhanced MRIs synovial thickening cannot be assessed and on these images synovitis has been inconsistently associated with pain. Objective To assess synovial thickening in relation to knee pain severity among subjects in the Multicenter Osteoarthritis Study (MOST) using contrast-enhanced (CE) MRI. Methods MOST is a cohort study of people who have, or are at high risk of, knee osteoarthritis (OA). An unselected subset of 535 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
216
1
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(232 citation statements)
references
References 10 publications
(13 reference statements)
9
216
1
4
Order By: Relevance
“…Additionally, the study considered the facility with which individuals expressed their painful condition, verifying that SCRP mean was higher in patients who had easier-to-elicit pain (5.21 ± 1.46 mg/l), than in patients in which elicit pain was difficult (3.46 ± 3.25 mg/l), however, this difference was not statistically significant. The results are in line with several studies carried out in humans, where it was possible to demonstrated the relationship between the DJD grade and it tissues changes such as, effusions, popliteal cysts, and synovial thickening, and the pain level exibit by the patients (Hill et al 2001;Conaghan et al 2006;Hill et al 2007;Baker et al 2010). Imaging is an important component for DJD stage characterization.…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, the study considered the facility with which individuals expressed their painful condition, verifying that SCRP mean was higher in patients who had easier-to-elicit pain (5.21 ± 1.46 mg/l), than in patients in which elicit pain was difficult (3.46 ± 3.25 mg/l), however, this difference was not statistically significant. The results are in line with several studies carried out in humans, where it was possible to demonstrated the relationship between the DJD grade and it tissues changes such as, effusions, popliteal cysts, and synovial thickening, and the pain level exibit by the patients (Hill et al 2001;Conaghan et al 2006;Hill et al 2007;Baker et al 2010). Imaging is an important component for DJD stage characterization.…”
Section: Discussionsupporting
confidence: 87%
“…Since cartilage loss on MRI may also reflect the influence of local inflammation, which may in turn be related to systemic inflammation [Baker et al 2010], authors also examined the relationships between cartilage loss and the n-6 and n-3 PUFA levels. Among the 472 subjects (average 60 years of age, mean BMI 30, 50% women), half of the subjects exhibited radiographic knee OA and one-third demonstrated synovitis on MRI.…”
Section: Insight Into the Pathophysiology Of Oa Revealed By Biochemicmentioning
confidence: 99%
“…Studies using nonenhanced MRI showed inconsistent results regarding an association between synovitis and knee pain. A recent report showed that synovitis detected by contrast-enhanced MRI had a strong association (adjusted odds ratio 9.2) with at least moderate severity of knee pain as assessed by the Western Ontario and McMaster Osteoarthritis Index pain scale [169]. A comprehensive whole-knee joint synovitis scoring system has been proposed recently, which showed a high reliability based on contrast-enhanced MRI [170].…”
Section: Mri In Osteoarthritismentioning
confidence: 99%